The Effectiveness of Research and Development in the Field of Transport and Space Systems in Russia: Analysis of Publication Activity - V. P. Zavarukhin; T. I. Сhinaeva; E. Yu. Churilova (Статистика и экономика, 2022)
The aim of the study. Federal target program “Research and development in priority areas of development of the scientific and technological complex of Russia for 2014-2021” defines transport and space systems as a priority area of strategic importance for the country’s economy. The aim of the work is to study the state of research and development in the field of study and development of transport and space systems based on performance analysis, as well as to compare the effectiveness of scientific activities of educational organizations of higher education and scientific organizations in this area.Materials and methods. The information base of the study was statistical data and analytical information reflecting the state of research and development in the field of study and development of transport and space systems. The methodological base of the study is statistical methods of information analysis: analysis of variance, testing of statistical hypotheses, non-parametric criteria for comparing samples, analysis of time series, structural analysis.Results and discussion. The article reflects the results of the Institute for the Study of Science of the Russian Academy of Sciences monitoring the scientific potential of organizations conducting research and development in the priority area of scientific and technological development “Connectedness of the territory of the Russian Federation through the creation of intelligent transport and telecommunication systems, as well as the occupation and retention of leadership positions in the creation of international transport and logistics systems, the development and use of outer space and air space, the World Ocean, the Arctic and Antarctic”. This publication, in particular, analyzes the effectiveness of research and development in the priority area “Transport and space systems”.As a result of the analysis, conclusions were drawn about the main directions and trends of research and development in the field of studying and developing transport and space systems in Russia for the period 2015-2019. With the help of methods of dispersion analysis, nonparametric criteria, etc., a comparison was made of the effectiveness of scientific activity of educational organizations of higher education and scientific organizations.The analysis showed that international publishing analytical systems occupy a greater weight in the volume of publications compared to the Russian Science Citation Index (RSCI).Researchers of educational organizations of higher education have 5 times more publications than employees of scientific organizations, which can be explained by overestimated requirements for positions of faculty and the formation of “garbage” articles. In terms of citation, 2017 was the most successful year for Russian researchers in the field of transport and space systems. At the same time, the citation of researchers from educational organizations was 3-3.5 times higher in international publications and twice as high in RSCI publications. Scientific organizations in the field of scientific, design, technological works show much greater effectiveness and efficiency compared to educational institutions of higher education. For the period 2015-2019 a trend towards a decrease in the results of intellectual activity was revealed for all organizations under consideration.The analysis also showed the low performance of small innovative enterprises in this priority area for the period 2015-2019. In Russia, they have not received proper development. Dispersion analysis, testing of statistical hypotheses using nonparametric methods made it possible to compare the results of the activities of scientific organizations and organizations of higher education.Conclusions. Thus, one of the ways to increase the efficiency and effectiveness of science in Russia can be attributed to the revival of the system of research institutes, the activities of which would be aimed at meeting the specific scientific needs of the state.